Pendapatan Usaha Tetes Tebu sebagai Pupuk Organik Cair di Desa Janti Kecamatan Papar Kabupaten Kediri - Utomo, Rizki Cahyo; Dianasari, Melinda Nur; Atika, Khofifa Nur; Winahyu, Nastiti (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
The by-product of processing sugar cane into sugar is molasses. Molasses is used as an liquid organic fertilizer which is applied to corn in Janti Village, Papar District, Kediri Regency. In addition to the demand for molasses, the large area of corn causes an increase in the demand for labor outside the family to apply the fertilization process. This causes the business of providing molasses liquid organic fertilizer to be developed by adding fertilizing labor services. The request is an opportunity for molasses business owners so it needs to be equipped with an analysis of income calculations for future business development. The purpose of this study is to analyze the income of molasses business. The research location was determined purposively with the consideration that the location is the only distributor of molasses in the area. Based on the results of the analysis, it is found that the business is feasible to run. The R/C analysis shows the result of 5.27 which means that every one unit of cost incurred will generate the revenue. The results show that the business is feasible to be developed. Break Event Point (BEP) rupiah of molasses liquid organic fertilizer business can break even at the price of Rp 231.00 per liter with BEP production of 63,208.06 liters per season.